2009
DOI: 10.1021/bm9006612
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 13C-Perlabeled Cellulose with more than 99% Isotopic Enrichment by a Cationic Ring-Opening Polymerization Approach

Abstract: (13)C-Perlabeled cellulose was obtained in a seven-step approach from (13)C(6)-labeled d-glucose with a cationic ring-opening polymerization as the key step. Isopropylidene protection, benzylation of the remaining free 3-O-position and subsequent deprotection afforded 3-O-benzyl-(13)C(6)-glucose (2). Regioselective bis-pivaloylation followed by subsequent ortho-esterification provided the precursor for the cationic ring-opening polymerization, 3-O-benzyl-(13)C(6)-glucopyranose 1,2,4-orthopivalate (4). The actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Similar to a puzzle where the arrangement of the individual pieces must fit to give the final picture, the number of furanoyl units per chromophore molecule and their linkage sites can be determined by this methodology, which was done for all five chromophores. The combination of isotopic labeling and NMR spectroscopy, as also used previously (Adelwöhrer et al 2009;Krainz et al 2010;Malz et al 2007), once more proved to be a powerful tool in chromophore research.…”
Section: Resultsmentioning
confidence: 93%
“…Similar to a puzzle where the arrangement of the individual pieces must fit to give the final picture, the number of furanoyl units per chromophore molecule and their linkage sites can be determined by this methodology, which was done for all five chromophores. The combination of isotopic labeling and NMR spectroscopy, as also used previously (Adelwöhrer et al 2009;Krainz et al 2010;Malz et al 2007), once more proved to be a powerful tool in chromophore research.…”
Section: Resultsmentioning
confidence: 93%
“…Cationic ring-opening copolymerization of glucose orthoester derivatives 2D and 2L Glucose orthoester derivatives 2D and 2L were synthesized from compounds 1D and 1L, respectively, according to previous reports (Adelwöhrer et al 2009, Yagura et al 2020). The ring-opening copolymerization of compounds 2D and 2L in a 1:1 ratio was conducted to give compound 3DL in quantitative yield.…”
Section: Resultsmentioning
confidence: 99%
“…Materials D-glucose (1D) and L-glucose (1L) were purchased from Nacalai Tesque Inc. (Kyoto, Japan) and Tokyo Chemical Industry Co. (Tokyo, Japan), respectively, and were dried in a vacuum desiccator under high vacuum (less than 1 hPa) at 70 C for 16 h before use. Compounds 2D and 2L were synthesized from compounds 1D and 1L, respectively, according to previous reports (Adelwöhrer et al 2009, Yagura et al 2020. Powdered 4 Å molecular sieves were activated in a GTO-2000 glass tube oven (Sibata Scientific Technology Ltd, Tokyo, Japan) Scheme 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Adelw€ ohrer et al [41] reported the successful synthesis of 13 Cperlabeled cellulose through an approach involving cationic ring-opening polymerization. As precursor, the authors used 3-O-benzyl-13 C 6 -glucopyranose 1,2,4-orthopivalate and obtained fully labeled 13 C-cellulose as the cellulose II allomorph, with a DP of 40 and an overall yield of 28%.…”
Section: Chemical Synthesismentioning
confidence: 99%